DEVELOPING AN EFFECTIVE EMPLOYER BRANDING STRATEGY AT ABC LIGHTING COMPANY FOR EARLY CAREERS THROUGH EMPLOYEE ADVOCACY - Rachman, Amelia Martia; Darmastuti, Ismi; Hasya, Afina (Diponegoro Journal of Management, 2023)
ABSTRACT This paper is written to carry out the required company research for Amelia Martia Rachman’s final graduation project in International Business at Diponegoro University, Indonesia and at Saxion University of Applied Sciences, Netherlands. This research paper focuses on assessing and developing the employer branding strategy for early career talents at ABC Lighting Company in order to develop an efficient plan as the company is currently looking for an appropriate approach to strengthen its brand awareness within potential early career talents. Desk research, including newspapers, articles, records of data, and a survey of 24 respondents regarding ABC Lighting Company’s employer branding efforts were conducted to obtain the data for this research. The findings of this study will be used to help the company develop a plan to improve its employer branding strategy to attract young professionals as well as to boost the intern-turnover rate into full-time employees. It will give a further insight into the key elements of an effective employer branding strategy, dimensions of employer branding, candidate journey funnel, effective employer branding channels for Generation Z, the characteristics and work values of Generation Z, as well as the potential challenges and opportunities for Generation Z-focused employer branding.